Effect of various growing media on growth and yield of lettuce in hydroponics system at Lalitpur, Nepal - Ghimire, S.; Giri, H.N.; Pandey, U.; Kafle, K.; Budha, S. (International Journal of Horticultural Science, 2026)
Hydroponic farming, particularly using the nutrient film technique, is gaining traction as a sustainable approach for cultivating leafy vegetables such as lettuce. However, the selection of appropriate growing media remains critical for optimizing plant growth and yield in a soilless system. A completely randomized design (CRD) was used in this study to assess the impact of six distinct growing media (sponge made up of cellulose, perlite, saw dust, sand, cocopeat, and rice husk) on the growth and yield of lettuce under NFT conditions at Mutha Agro Pvt. Ltd., Lalitpur, Nepal. Analysis of variance (ANOVA) in RStudio (v4.4.1) was used to examine the data, and Tukey HSD test was used to differentiate treatment means at a 5% significance level. Lettuce grown in sponge media exhibited the highest performance in terms of number of leaves (11), longest leaf length (17.55 cm), greatest leaf width (9.43cm), plant height (35.81 cm), root length (12.51 cm), canopy diameter (36.07 cm), and stem diameter (0.62 cm). The highest fresh root weight (24.67 g) and moisture loss (98.7%) were obtained by perlite. The highest yield was recorded in sponge (146.45 g), followed by perlite (139.65 g), while the lowest was observed in rice husk (117.83 g). Overall, sponge made up of cellulose proved to be the most effective growing medium for hydroponic lettuce cultivation using NFT, followed by perlite. These findings can help guide growers in selecting suitable substrates to improve yield and quality in hydroponic production systems.